Changes in speech-related brain activity during adaptation to electro-acoustic hearing - Balkenhol, Tobias; Wallhäußer-Franke, Elisabeth; Rotter, Nicole; Servais, Jérôme J. (Frontiers in neurology, 2020)
Objectives: Hearing improves significantly with bimodal provision, i.e. a cochlear implant (CI) at one ear and a hearing aid (HA) at the other, but performance shows a high degree of variability resulting in substantial uncertainty about the performance that can be expected by the individual CI user. The objective of this study was to explore, how auditory event-related potentials (AERP) of bimodal listeners in response to spoken words approximate the electrophysiological response of normal hearing (NH) listeners. Study Design: Explorative prospective analysis during the first 6 months of bimodal listening using a within-subject repeated measures design. Setting: Academic tertiary care center. Participants: Twenty-seven adult participants with bilateral sensorineural hearing loss who received a HiRes 90K CI and continued use of a HA at the non-implanted ear. Age-matched NH listeners served as controls. Intervention: Cochlear implantation. Main Outcome Measures: Obligatory auditory evoked potentials N1 and P2, and the event-related N2 potential in response to monosyllabic words and their reversed sound traces before, as well as 3 and 6 months post-implantation. The task required word/non-word classification. Stimuli were presented within speech-modulated noise. Loudness of word/non-word signals was adjusted individually to achieve the same intelligibility across groups and assessments. Results: Intelligibility improved significantly with bimodal hearing, and the N1-P2 response approximated the morphology seen in NH with enhanced and earlier responses to the words as compared to their reversals. For bimodal listeners, a prominent negative deflection was present between 370 ms and 570 ms post stimulus onset (N2), irrespective of stimulus type. This was absent for NH controls, hence this response did not approximate the NH response during the study interval. N2 source localization evidenced extended activation of general cognitive areas in frontal and prefrontal brain areas in the CI group. Conclusions: Prolonged and spatially extended processing in bimodal CI users suggests employment of additional auditory-cognitive mechanisms during speech processing. This does not reduce within 6 months of bimodal experience and may be a correlate of the enhanced listening effort described by CI listeners.